Public involvement and health research system governance: a qualitative study - Fiona Alice Miller; Sarah J. Patton; Mark Dobrow; Deborah A. Marshall; Whitney Berta (BMC, 2018)
Abstract Background Interest in public involvement in health research projects has led to increased attention on the coordination of public involvement through research organisations, networks and whole systems. We draw on previous work using the 'health research system' framework to explore organisational actors and stewardship functions relevant to governance for public involvement. Methods To inform efforts in Ontario, Canada, to mobilise public involvement across the provincial health research enterprise, we conducted an exploratory, qualitative descriptive study of efforts in two jurisdictions (England, United Kingdom, and Alberta, Canada) where there were active policy efforts to support public involvement, alongside jurisdiction-wide efforts to mobilise health research. Focusing on the efforts of public sector organisations with responsibility for funding health research, enabling public involvement, and using research results, we conducted in-depth, semi-structured interviews with 26 expert informants and used a qualitative thematic approach to explore how the involvement of publics in health research has been embedded and supported. Results We identified three sets of common issues in efforts to advance public involvement. First, the initial aim to embed public involvement leveraged efforts to build self-conscious research 'systems', and mobilised policy guidance, direction, investment and infrastructure. Second, efforts to sustain public involvement aimed to deepen involvement activity and tackle diversity limitations, while managing the challenges of influencing research priorities and forging common purpose on the evaluation of public involvement. Finally, public involvement was itself an influential force, with the potential to reinforce - or complicate - the ties that link actors within research systems, and to support - or constrain - the research system's capacity to serve and strengthen health systems. Conclusions Despite differences in the two jurisdictions analysed and in the organisation of public involvement within them, the supporters and stewards of public involvement sought to leverage research systems to advance public involvement, anticipated similar opportunities for improvement in involvement processes and identified similar challenges for future involvement activities. This suggests the value of a health research system framework in governance for public involvement, and the importance of public involvement for the success of health research systems and the health systems they aim to serve.